Secure System Design and Trustable Computing 2016
DOI: 10.1007/978-3-319-14971-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Secure Licensing of IP Cores on SRAM-Based FPGAs

Abstract: The rapid increase in FPGA devices' capacity has enabled the implementation of complete sophisticated systems. The widening design productivity gap and shrinking time-to-market window have made licensing of external IP cores for system development pervade. The upfront IP licensing model currently used in the market is not a good fit to the FPGA IP market as the blanket IP license fee is too expensive for the majority of FPGA-based system developers who target low-to-medium volume applications. This chapter pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Due to the property of being unclonable and tamper-proof, the PUF enables effective IP licensing schemes [55][56][57]. A detailed review of both types of schemes can be found in [58]. This thesis will focus on the former type of IP licensing schemes, i.e., the conventional crypto primitives based type.…”
Section: Active Control Of the Ip Usagementioning
confidence: 99%
“…Due to the property of being unclonable and tamper-proof, the PUF enables effective IP licensing schemes [55][56][57]. A detailed review of both types of schemes can be found in [58]. This thesis will focus on the former type of IP licensing schemes, i.e., the conventional crypto primitives based type.…”
Section: Active Control Of the Ip Usagementioning
confidence: 99%